SPCR-01 RAPIDPLAN HIPPOCAMPAL SPARING WHOLE BRAIN MODEL VERSION 2 - HOW FAR CAN WE REDUCE THE DOSE?. (5th August 2022) - Liu, Hefei; Clark, Ryan; Magliari, Anthony; Foster, Robert; Reynoso, Francisco; Schmidt, Matthew; Gondi, Vinai; Abraham, Christopher; Curry, Heather; Kupelian, Patrick; Khuntia, Deepak; Beriwal, Sushil
Abstract: BACKGROUND: Whole-brain radiotherapy (WBRT) has been the standard palliative treatment for patients with brain metastases due to its effectiveness, availability, and ease of administration. Recent clinical trials have shown that limiting radiation dose to the hippocampus is associated with decreased cognitive toxicity. In this study, we updated an existing Knowledge Based Planning (KBP) model to further reduce dose to the hippocampus and improve other dosimetric plan quality characteristics. METHODS: 42 clinical cases were contoured according to NRG-CC001 guidelines. A new dosimetric scorecard was created as an objective measure for plan quality. The new Hippocampal Sparing Whole Brain Version 2 (HSWBv2) model adopted a complex recursive training process and was validated with five additional cases. HSWBv2 treatment plans were generated on the Varian Halcyon TM and TrueBeam TM systems and compared against plans generated from the existing (HSWBv1) model released in 2016. RESULTS: On the Halcyon TM platform, 42 cases were re-planned. Hippocampal D100% from HSWBv2 and HSWBv1 models had an average dose of 5.75 Gy and 6.46 Gy, respectively (p<0.001). HSWBv2 model also achieved a hippocampal Dmean of 7.49 Gy, versus 8.10 Gy in HSWBv1 model (p<0.001). Hippocampal D0.03CC from HSWBv2 model was 9.86 Gy, in contrast to 10.57 Gy in HSWBv1 (p<0.001). For PTV_3000, D98% and D2% from HSWBv2 model were 28.27 Gy and 31.81 Gy, respectively, compared to 28.08 Gy (p=0.020) and 32.66 Gy from HSWBv1 (p<0.001). Among several other dosimetric quality improvements, there was a significant reduction in PTV_3000 V105% from 35.35% (HSWBv1) to 6.44% (HSWBv2) (p<0.001). On five additional validation cases, dosimetric improvements were also observed on TrueBeam TM . CONCLUSION: In comparison to published data in addition to the HSWBv1 model, the HSWBv2 model achieved higher quality HA-WBRT treatment plans through further reductions in hippocampal dose while improving target coverage and dose conformity/homogeneity. HSWBv2 model is shared publicly.